(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The pandemic diseas have been minatory in accordance with racial health, and certain is associated according to the excessive price concerning fulfillment along apprehending the residences sib confusion generation amongst the humans want in conformity with aid to us in a while absorbing half uncommon measures of accordance together with cease or government idee fixe spreading. In that paper, we endorse a contemporary confusion mannequin via mastership about the utilization concerning two-layer a couple about networks since inspecting an associate of having an have an effect on involving interest embrace due to the fact that turmoil propagation, the area the acme seam represents the focal point attachment regarding epidemics but the government tier expresses the pandemic diseas propagation. In the method regarding focus diffusion, the naught individual’s want remains conscious concerning the epidemics proviso the ratio amongst theirs consciousness neighbors but their tiers reaches the unique ratio. For the idee fixe distillation regarding the decrease layer, we makes use of the amazing SIR (susceptible-infected-recovered), model. We infer the epidemic graduation by means of the use of road in regard to the usage concerning the Micro-Markov approach. The analytical outcomes indicate of afterwards want the epidemic graduation is correlated collectively along the core on attention embody namely as nicely as like the topology of affinity to pandemic disea networks. Finally, the simulation consequences further display the residences related in imitation of assault generation since attempt the analytical results.